Tipos de apego y su incidencia en la autoestima de las madres adolescentes que acuden al hospital pediátrico Alfonoso Villagómez Román de Riobamba periodo Diciembre 2015-Mayo 2016 - Quintanilla Pazmiño, Pedro Daniel (2016)
The title of this research is: “Types of attachment and its impact on self-esteem of adolescent mothers who attend the Pediatric Hospital Alfonso Villagomez Roman of Riobamba city, in the period December 2015-May 2016”. The general objective is to determine the incidence of the type of attachment esteem of teenage mothers who attend the Pediatric Hospital Alfonso Villagomez Roman in Riobamba city. The population that was studied were all adolescent mothers who attended the hospital in the period of investigation who were in total 30 people. The research design is transversal. It is a field research and the level of research is descriptive. There were used psychological questionnaires as data collection technique, the instruments used were: Questionarie CaMir to determine the type of adolescent attachment and Rosenberg scale to define the level of self-steem. After it was conducted the research process the following results were obtained: From the 100% of the population it is observed that there is a direct relationship between the type of attachment and self-esteem for this reason the results that correspond to the 50% of adolescents that have proportional disorganized attachment to 53.33% with low self-esteem; the 40% shows preoccupied attachment that correspond to the 36.66% who have an average of self-esteem; finally the 6.66% has an avoidant 6.66% and the 3.33% have insurance, proportional to the 10% of the population with high self-esteem attachment. It is possible to observe that attachment and self-esteem go together in regard to relationships. At the end of the investigation, it was perfomed an intervention model to improvate the level of self-esteem, addressed to teenage mothers who attend the Pediatric Hospital Alfonso Villagomez Roman city of Riobamba. It was performed with a cognitive approach based on the type of attachment and through strategies to improve self-esteem for the benefit of mental health and quality of life of adolescent mothers.